NIOSOMES AS AN EMERGING FORMULATION TOOL FOR DRUG DELIVERY-A REVIEW - S., SARASWATHI T.; M, MOTHILAL; K., JAGANATHAN M. (International Journal of Applied Pharmaceutics, 2019)
Nonionic surfactant based vesicles which are uni/multilamellar in structures are called niosomes. These vesicles contains an aqueous interior surrounded by one or more amphiphilic bilayer membrane forming surfactant which separates them from the bulk solution, and are also called as supramolecular aggregates. Niosomes, being an efficient drug delivery system, investigations are carried out to utilize this system to treat various disorders, to promote improved patient compliance, lesser side effects, reduction in dose, lesser dosage frequency, and higher amount of the drug at the particular site so as to lessen an excessive contact with the whole body. The Pharmacokinetic and Pharmacodynamic profile of Niosomal drug delivery system vary for various entrapped drugs. Drugs that are successful in the mitigation or treatment of CNS disorders should cross the BBB to reach the brain, as BBB seems to be an obstacle for a large number of drugs, including CNS active drugs. This article compiles recent techniques for the preparation and characterization of niosomes, the effect of formulation variables on its physicochemical properties and discussed about its effective applications in drug delivery.